Environmental Risks Associated With Urban Development Projects in Kenya - Mburu, Janet (International Journal of Modern Risk Management, 2024)
Purpose: The aim of the study was to examine environmental risks associated with urban development projects in Kenya Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study revealed that urban development projects in Kenya present significant environmental risks that require careful consideration and proactive mitigation measures. The rapid urbanization and infrastructure expansion in Kenya's cities have been associated with various environmental challenges, including air and water pollution, habitat loss, soil degradation, urban heat island effects, and adverse impacts on human health. These environmental risks stem from factors such as increased vehicular emissions, industrial activities, improper waste management practices, deforestation, and inadequate urban planning and infrastructure. The concentration of population and economic activities in urban centers exacerbates these environmental pressures, further highlighting the urgent need for sustainable urban development strategies in Kenya. Unique Contribution to Theory, Practice and Policy: urban political ecology theory, environmental justice theory & sustainable development theory may be used to anchor future studies on environmental risks associated with urban development projects in Kenya. Prioritize the implementation of green infrastructure initiatives, such as green roofs, urban parks, and sustainable drainage systems, to mitigate environmental risks associated with urban development. Integrate nature-based solutions into urban planning and design processes to enhance ecosystem services, improve air and water quality, and reduce urban heat island effects. Advocate for legislative reforms and policy interventions that prioritize environmental sustainability in urban development planning and regulation. Implement stringent environmental impact assessment (EIA) processes for all urban development projects to ensure compliance with environmental standards and regulations.